The Spermicide Effect from Methanol Extract of Kalangkala Seed (Litsea angulata) to Spermatozoa Mice (Mus musculus) - Rommy Akmal; Kuswanto Kuswanto; Syarifah Fahrunnisa; Ridha Aulia Rahmi; Nur Ema Putri Bayanil; Anni Nurliani (Journal of Agromedicine and Medical Sciences, 2016)
Men involvement in family planning needs to be increased by providing natural spermicide from natural source which is safer. One of them is kalangkala seed which is endemic plant in South Kalimantan. The spermicide effect from methanol extract of kalangkala seed to mice spermatozoa was studied in this research by in vitro method. Spermatozoa suspension was taken from epididymis cauda of twenty five male Balb/c mice. This research used a complete randomized design with five treatments i.e control which without any addition; spermatozoa suspension + NaCMC 0.5%; spermatozoa suspension + methanol extract of kalangkala seed 0.1%; spermatozoa suspension + methanol extract of kalangkala seed 0.3%; and spermatozoa suspension + methanol extract of kalangkala seed 0.5% with five repetitions for each treatment. The result of this study showed that methanol extract of kalangkala seed caused decrease of motility and movement velocity mice spermatozoa until achieve zero value in 0.5% concentration. Key words: kalangkala seed, mice, spermatozoa, natural spermicide